The Influence of Empathy, School Climate, and Peer Support on Anti-Bullying Behavior among High School Students in Jeneponto Regency - Muh Amar; Andi Kasmawati; Mustaring Mustaring; Bakhtiar Bakhtiar; Najamuddin Najamuddin (Universitas Muhammadiyah Metro, 2026)
Bullying is a serious problem in educational settings that negatively affects students’ psychological and social well-being. Anti-bullying behavior is influenced by various psychological and social factors, including empathy, school climate, and peer support. This study aimed to analyze the effects of empathy, school climate, and peer support on anti-bullying behavior among public senior high school students in Jeneponto Regency. This study employed a quantitative approach using multiple linear regression analysis. The sample consisted of 109 students selected through proportionate stratified random sampling. Data were collected using Likert-scale questionnaires and analyzed using SPSS. The results showed that empathy had a positive and significant effect on anti-bullying behavior (B = 0.166; t = 2.235; p = 0.028), school climate also had a positive and significant effect (B = 0.206; t = 2.349; p = 0.021), and peer support had a positive and significant effect and was identified as the most dominant predictor (B = 0.641; t = 7.571; p < 0.001). Simultaneously, empathy, school climate, and peer support significantly influenced anti-bullying behavior (F = 176.922; p < 0.001), with a coefficient of determination (RÂ²) of 0.835, indicating that these variables explained 83.5% of the variance in students’ anti-bullying behavior. These findings indicate that anti-bullying behavior is influenced by the interaction between individual psychological factors and social environmental factors. This study highlights the importance of strengthening empathy, fostering a positive school climate, and enhancing peer support in promoting anti-bullying behavior among students.